Burden of influenza in adults with cardiac arrest admissions in Australia. (15th August 2022) - Moa, Aye; Tan, Timothy; Wei, Jenny; Hutchinson, Danielle; MacIntyre, C. Raina
Abstract: Background: Cardiac arrest is the least preventable burden of cardiovascular disease, as treatment depends on timely resuscitation. The incidence of sudden cardiac arrest (SCA) is high, contributing 10–20% of cardiovascular mortality globally. The influenza vaccine reduces the risk of acute cardiovascular events. Little is known about the relationship of influenza infection to cardiac arrest. Methods: This study aimed to determine the estimated rate of SCA hospitalisations attributable to influenza in Australian adults. A generalised-additive statistical model was applied in the study. Weekly counts of laboratory-confirmed influenza notifications were used as independent variables in the model. Results: Our estimates showed that the yearly rate of SCA hospitalisations varied, and a significant association with influenza was observed in some years in older adults aged 65 years and over. On average, the annual estimated SCA hospitalisations rate due to influenza in adults aged 50–64 years and ≥ 65 years were 0.7 (95%CI: 0.4, 1.1) and 5.3 (95%CI: 4.4, 6.2) per 100, 000 population, respectively. Conclusion: The association between influenza and SCA is evident in adults and the disease burden is significant in older people. Prevention of influenza by vaccination may reduce SCA. Highlights: The peak cardiac arrest hospitalisations overlapped with the seasonal peak of influenza cases. The association between influenza and sudden cardiac arrest (SCA) is highest in adults 65 years and older. Understanding the cardiac burden attributable to influenza could inform the use of influenza vaccine to reduce SCA in adults.